Building Financial Resilience : Lessons Learned from the Early Impact of COVID-19 on Water and Sanitation Service Providers in Latin America - Makino, Midori; Serrano, Hector; Flores, Berenice; Hurtado, Jaime (World Bank, Washington, DC, 2021)
While the coronavirus disease (COVID-19) pandemic reinforced the critical role that water supply and sanitation (WSS) plays in preventing its spread, it affected the financial stability of service providers in the industry. In response to demands from the client countries, the World Bank carried out an analytical service and advisory (ASA) activity to assess the financial impact of the Coronavirus (COVID-19) pandemic on WSS service providers in Latin America and identify possible mechanisms to improve service providers’ resilience to these external shocks. This report presents the key findings from the financial impact assessment of the Coronavirus (COVID-19) pandemic on WSS service providers in Latin America and draws cross-cutting lessons. The report also documents examples of good practices that can be implemented at the WSS service provider and government levels to build the financial resilience of the sector and lays out some financing mechanisms that can help service providers enhance their capacity to cope with future pandemics or other crises, including natural disasters. It is envisioned that the findings of this report will inform policymakers and WSS service providers in the World Bank’s client countries in planning for financial resilience building in the WSS sector.